Oral hygiene in the control of occlusal caries in newly erupted first permanent molars. - Arrow, Peter G. (Curtin University, 1997)
Caries of the pits and fissures of permanent teeth continues to be a problem for children. Newly erupted permanent molars are particularly at risk. Oral hygiene measures have been shown to be able to reduce the incidence of caries. The aim of this study was to compare the caries preventive effects of a professional tooth cleaning and oral health education programme (test) with a standard preventive programme (comparison), comprising selective fissure sealing and application of topical fluorides on newly erupted first permanent molars. School Dental Service clinics of the Health Department of Western Australia, in Perth, were assigned to test (4)or comparison (4) clinics. Schoolchildren, mean age 6.3 plus or minus 0.3 (s) yr with, sound, newly erupted first permanent molars were included in the study (n=404; 207 test; 197 control).Children were examined after twelve and twenty-four months by an examiner who was 'blind' to the test or control status of the children. After twelve months, 186 test and 163 control children were examined, and after twenty-four months, 179 test and 156 control children were examined. Three hundred and twenty children were examined in both years. After twenty-four months, 32 children in test and 31 children in control developed caries of the first permanent molars, the estimated risk ratio was 0.90 (95% CI 0.58, 1.41); and children in the test group had an average DFT score of 0.30 plus or minus 0.75 compared with 0.30 plus or minus 0.70 DFT in the control group (t-test, p=0.96). The results suggest that, after two years, there was no statistically significant difference between the caries preventive effects of a professional tooth cleaning and oral health education programme and a programme based on selective fissure sealing and application of topical fluorides.Baseline deciduous caries experience, presence of hypomineralised first permanent molars and frequency of toothbrushing were statistically significant factors in predicting molar caries. Using baseline deciduous caries experience as a screening criterion to predict permanent molar caries, sensitivity of 0.67 and specificity 0.61 were obtained at a cutpoint of 1 dmfs. Sensitivity and specificity values were maximised at 0.72 by using a combined baseline dmfs and hypomineralisation as screening criteria. Cost-effectiveness analysis indicated an incremental cost-effectiveness ratio of $40/child/year. The test programme was more costly and produced similar outcomes and does not warrant adoption on economic grounds.